An exploratory association study of the influence of noradrenergic genes and childhood trauma in Borderline Personality Disorder. Issue 1 (30th September 2015) - Martín-Blanco, Ana; Ferrer, Marc; Soler, Joaquim; Arranz, Maria Jesús; Vega, Daniel; Bauzà, Joana; Calvo, Natalia; Elices, Matilde; Sanchez-Mora, Cristina; García-Martinez, Iris; Salazar, Juliana; Ribases, Marta; et al.
Abstract: This study investigated the possible association of 40 polymorphisms within 4 noradrenergic genes with BPD risk and the modulating effect of childhood trauma on these associations in 481 BPD subjects and 442 controls. COMT rs5993882, DBH rs77905 and SLC6A2 rs1814270 showed associations with BPD, which were modulated by childhood trauma. However, none of these findings survived Bonferroni correction. Further investigation is needed to clarify the involvement of these genes in BPD pathogenesis. Highlights: COMT rs5993882, DBH rs77905 and SLC6A2 rs1814270 were asociated with BPD risk. This association was modulated by the presence of childhood traumatic events. Results suggest a possible contribution of noradrenergic genes to BPD pathogenesis. This study supports the involvement of gen-environment interactions in BPD aetiology.